Pre-exposure prophylaxis in the era of emerging methods for men who have sex with men in the USA: the HIV Prevention Cycle of Care model. Issue 2 (February 2023) - Mansergh, Gordon; Sullivan, Patrick S; Kota, Krishna Kiran; Daskalakis, Demetre
Summary: Expanding on previous work, we present an HIV Prevention Cycle of Care model to facilitate understanding of the complexity of issues involved in pre-exposure prophylaxis implementation for gay, bisexual, and other men who have sex with men (MSM) in the USA, including individual, client–provider, and overarching issues such as health equity, stigma, and prevention nomenclature. The HIV prevention cycle of care applies to MSM who test negative for HIV. The Prevention Cycle of Care model includes seven steps: prevention knowledge, prevention self-awareness and preferences, prevention motivation, health-care access and cost, provider issues, adherence and persistence, and periodic reassessment and adjustment. HIV prevention is complex in an era of emerging multiple modalities, and more research is needed to successfully implement pre-exposure prophylaxis options over time and across diverse communities of MSM who are sexually active.